Identification of Underground Rivers Using Very Low Frequency Electromagnetic and Graphical User Interface Matrix Laboratory: Implications for Groundwater Exploration - Umam, Rofiqul; Sismanto, Sismanto; Umar, Emi Prasetyawati; Siregar, Rahmat Nawi; Maula, Frida Yassar; Takahashi, Hirotaka (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
The research aims to detect underground rivers using 2D mapping and minimal-noise data. In this research, 2-dimensional (2D) mapping of underground rivers in karst areas was carried out using the geophysical method of very low-frequency electromagnetic waves, namely VLF-EM (Very Low Frequency Electromagnetic Method). Electromagnetic wave analysis is based on differences in object frequencies, which reflect subsurface resistivity and conductivity and are captured by the VLF-EM detector. The measurement results were analyzed using three filter equations (Moving Average, Fraser, and Karous H-Jelt) and the Graphics User Interface Matrix Laboratory (GUI-MatLab) Software. Apart from that, the use of GUI-MatLab aims to create VLF-EM data processing software that is better for 2D interpretation display and more efficient in processing (requiring data entry only once). The research area was located in the karst rock area of Gunung Kidul Regency, Yogyakarta, Indonesia, at coordinates 8.020°S and 110.36°E. The VLF-EM measurements and GUI-MatLab interpretation detected the presence of underground river flow crossing three villages in the study area (Timun Sari, Mojo Sari, and Peyuyon), with accurate results (conductive objects were easily distinguished). Therefore, based on this study, it is recommended that productive boreholes be drilled in the 3 villages where VLF measurements were taken. The productive borehole drilling is recommended in 3 villages.